Seasonal Variation in Respiratory and Photosynthetic Parameters in Three Mosses from the Maritime Antarctic - DAVEY, MARTIN C.; ROTHERY, PETER (Annals of Botany, 1996)
Carbon fixation under controlled conditions was measured in three mosses from the maritime Antarctic using an infra-red gas analysis system. Gas exchange parameters were determined during each season in 1993 and 1994 using the Arrhenius equation and a hyperbolic tangent function applied to respiration and photosynthesis, respectively. Environmental data was collected in 1994 for comparison. All seasonal variations were greater in Brachythecium than in the species from less hydric habitats. Respiration rates were highest in summer and lowest in winter at all temperatures in Brachythecium , but there was little change in Chorisodontium or Andreaea . There was some seasonal variation in the initial slope (K p ) of the photosynthesis-irradiance curve in all species, although the environmental data suggested that this was of little ecological importance. In all species seasonal changes in the maximum rates of photosynthesis (GP max , NP max ) were observed, generally with a pattern of summer maxima, although there were some interannual differences. These changes are considered to be the most important in affecting the overall annual productivity of the mosses. There were no seasonal variations in the optimum temperatures for either gross or net photosynthesis, or for the irradiance at the onset of light saturation (I k ). The results have important implications for the use of models to estimate the productivity of the Antarctic flora based upon present or predicted climate data.